2014
DOI: 10.1002/2013jg002429
|View full text |Cite
|
Sign up to set email alerts
|

Natural and human influences on dissolved silica export from watershed to coast in Southeast China

Abstract: Natural and human factors controlling dissolved silica (DSi) export from the watershed were investigated for the Jiulong River watershed in Southeast China, which is a subtropical region where tectonic activity and high runoff combine to create a global hot spot for DSi flux. Results showed that river DSi was fairly high (246 ± 76 μmol L À1 ) due to granite lithology and increased human perturbation. The percentage of granite, paddy soil, arable land, and forest land each explain 47-69% of the spatial variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Prior studies in temperate and sub‐tropical watersheds have found land cover to control DSi fluxes to coastal systems (Carey & Fulweiler, ; Chen et al, ; Clymans et al, ; Struyf et al, ). In lower latitude temperate and sub‐tropical systems, increasing forest cover is often associated with lower exports, which is attributed to sequestration of DSi in terrestrial vegetation (Carey & Fulweiler, ; Carey & Fulweiler, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies in temperate and sub‐tropical watersheds have found land cover to control DSi fluxes to coastal systems (Carey & Fulweiler, ; Chen et al, ; Clymans et al, ; Struyf et al, ). In lower latitude temperate and sub‐tropical systems, increasing forest cover is often associated with lower exports, which is attributed to sequestration of DSi in terrestrial vegetation (Carey & Fulweiler, ; Carey & Fulweiler, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in temperate and sub-tropical watersheds have found land cover to control DSi fluxes to coastal systems (Carey & Fulweiler, 2012b;Chen et al, 2014;Clymans et al, 2016;Struyf et al, 2010). In lower latitude temperate and sub-tropical systems, increasing forest cover is often associated with lower exports, which is attributed to sequestration of DSi in terrestrial vegetation (Carey & Fulweiler, 2012b;Carey & Fulweiler, 2013;Chen et al, 2014). Contrary to these lower latitude systems, we find the opposite trend here, as increasing basin forest coverage is associated with significantly higher DSi concentrations and yields ( Figure S2), a signal that corresponds well with those from the sub-Arctic region just south of our study region (Phillips & Cowling, 2019).…”
Section: Hydrologic Versus Biologic Drivers Of Watershed Dsi Exportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Si content varies with plant type, LULC is a critical determinant of the magnitude and timing of DSi export from terrestrial to aquatic systems Carey & Fulweiler 2013b). Thus, while geochemical factors undoubtedly play a key role in dictating Si fluxes (West, Galy & Bickle 2005;Jansen et al 2010), land cover can be on par in controlling DSi fluxes in temperate (Struyf et al 2010;Carey & Fulweiler 2012a) and tropical (Chen et al 2014) systems. For example, watersheds with aggrading forest cover export less DSi compared to their urban counterparts (Carey & Fulweiler 2012a), due in part to Si sequestration by vegetation (Conley 2002;Fulweiler & Nixon 2005;) and enhanced Si export from urban systems (Sferratore et al 2006).…”
Section: S I I N T E R R E S T R I a L P L A N T Smentioning
confidence: 99%
“…; Carey & Fulweiler ) and tropical (Chen et al . ) systems. For example, watersheds with aggrading forest cover export less DSi compared to their urban counterparts (Carey & Fulweiler ), due in part to Si sequestration by vegetation (Conley ; Fulweiler & Nixon ; Cornelis et al .…”
Section: Introductionmentioning
confidence: 99%